2008
DOI: 10.1016/j.freeradbiomed.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered 8-oxoguanine glycosylase in mild cognitive impairment and late-stage Alzheimer's disease brain

Abstract: Eight-hydroxy-2'-deoxyguanosine (8-OHdG) is increased in the brain in late-stage Alzheimer's disease (LAD) and mild cognitive impairment (MCI). To determine if decreased base-excision repair contributes to these elevations, we measured oxoguanine glycosylase 1 (OGG1) protein and incision activities in nuclear and mitochondrial fractions from frontal (FL), temporal (TL), and parietal (PL) lobes from 8 MCI and 7 LAD patients, and 6 age-matched normal control (NC) subjects. OGG1 activity was significantly (P<0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 52 publications
(80 reference statements)
1
69
0
Order By: Relevance
“…Recently, Shao et al [16] showed that intranuclear 8-OHdG levels from frontal, temporal, and parietal lobes were elevated in AD patients comparison to healthy controls. The plasma and urine levels of 8-OHdG in AD patients are significantly higher than those of controls [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Shao et al [16] showed that intranuclear 8-OHdG levels from frontal, temporal, and parietal lobes were elevated in AD patients comparison to healthy controls. The plasma and urine levels of 8-OHdG in AD patients are significantly higher than those of controls [31].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, immunochemical examination demonstrated that brain tissues from AD patients have between 1.2 and 3.1 times higher levels of intranuclear 8-hydroxy-2 0 -deoxyguanosine (8-OHdG) than control tissue [14][15][16]. Superoxide dismutase catalyzes the conversion of reactive oxygen to oxygen and hydrogen peroxide; the latter is decomposed to oxygen and water by the enzymes catalase and glutathione peroxidase.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased OGG1 activity and increased 8-oxoG content in the brain were found to be correlated with development of Alzheimer's disease and cognitive impairment [Iida et al, 2002;Wang et al, 2005;Mao et al, 2007;Shao et al, 2008;Dorszewska et al, 2009]. Interestingly, while one of these studies reported a specific increase in the mitochondrial OGG1-2a isoform in brains exhibiting the pathological state [Iida et al, 2002], another study did not observe an increase in the mitochondrial OGG1 protein content [Shao et al, 2008]. Despite these reported correlations between OGG1 and Alzheimer's disease in human cohorts, there is a lack of studies on Alzheimer's susceptibility using any of the multiple OGG1-deficient or overexpressing mouse models.…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Numerous studies exhibit an increase in oxidative DNA damage in the brain's of subjects with AD [25]. The greatest marked DNA adduct defined is 8-hydroxy-2-deoxyguanosine (8-OHdG) [26]. On the other hand advanced glycation end products are produced due to posttranslational modifications of proteins and may play a role in AD that is connected to oxidative modifications of Aβ peptides and tau [27].…”
Section: Introductionmentioning
confidence: 99%